The European Union Artificial Intelligence Strategy - Marsili, M.; Borges, J. (Ciência 2021, 2021)
Artificial intelligence (AI) is becoming one of the most important technologies of our time (OSCE, 2019) and is one of the most important economic and social developments in history, characterized as the lynchpin of the Fourth Industrial Revolution (Schwab, 2017). Military applications of AI are pushing forward the capacity for warfare and will transform its nature. Military robots that incorporate AI will play a greater role in the future (Cummings, 2017). A future battle might be ‘algorithms vs. algorithms’, with the best algorithm victorious. The European Union (EU) is also taking action on AI.